Effects of the climate elements on the decomposition of the litter in the Mata Atlântica forest at Alagoas State - Querino, Carlos Alexandre Santos; Vaz, Marcos André Braz; Querino, Juliane Kayse Albuquerque da Silva; Andrade, Antonio Marcos Delfino de; Moura, Marcos Antônio Lima (Revista do Departamento de Geografia, 2023)
The Mata Atlântica forest is one of the most worldwide deforested ecosystems. This ecosystem survives in small fragments that still plays an important role in the litter decomposition. The main aim of this paper was to verify the influence of climate elements in the seasonal deposition of litter and its decomposition in a fragment of Mata Atlântica. The study was carried out throughout October/2009 to March/2019. The data of Downward Radiation and Rainfall were stored every 10 minutes and collected in a Forest Reserve in Coruripe, Alagoas State. The normal litter had been monthly collected by nylon mesh meanwhile the accumulated litter was collected each 3 moths by metal collectors. All the collected materials were drought, weighted and quantified in Mg ha-1. It was estimated the decomposition rate, the average time of the accumulated litter renew and the necessary time (year) to the extinction of 50% (T0,5) and 95% (T0,05) of litter. The annual average of rainfall was 1233,92 mm. The average of downward solar radiation was 437,92 W m-2. The litter production was seasonal with lowest accumulation during the wet season and highest in the dry season. The decomposition coefficient average was 0,71 and the average time necessary to the extinction of 50 and 95% of the litter was, respectively, 1 and 4,2 years. Thus, stood out the seasonality of the production and accumulation of the total litter and its association with the rainfall regime.